Rainstorm on SGS - Unidentified photographer (Colorado State University. Libraries, 2003)
Shows rain falling on isolated spot on SGS, very small digital file, there should be a physical slide of this in archive.
Keywords: landscapes; rainstorm; grasslands; SGS